2004
DOI: 10.1021/jm049647a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altering the Electronics of 2-Methoxyestradiol on Cell Proliferation, on Cytotoxicity in Human Cancer Cell Cultures, and on Tubulin Polymerization

Abstract: A series of new analogues of 2-methoxyestradiol (1) were synthesized to further elucidate the relationships between structure and activity. The compounds were designed to diminish the potential for metabolic deactivation at positions 2 and 17 and were analyzed as inhibitors of tubulin polymerization and for cytotoxicity. 17alpha-methyl-beta-estradiol (30), 2-propynyl-17alpha-methylestradiol (39), 2-ethoxy-17-(1'-methylene)estra-1,3,5(10)-triene-3-ol (50) and 2-ethoxy-17alpha-methylestradiol (51) showed similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…The dependence of the reaction on the chain length may at least partially explain why 6-shogaol reduces the content of SH groups in tubulin more than 3-nonen-2-one. Previous reports have suggested that steric effects are involved in interactions with tubulin [17][18][19]. The chain length may be important for a,b-unsaturated carbonyl compounds to penetrate the interior of tubulin.…”
Section: Resultsmentioning
confidence: 99%
“…The dependence of the reaction on the chain length may at least partially explain why 6-shogaol reduces the content of SH groups in tubulin more than 3-nonen-2-one. Previous reports have suggested that steric effects are involved in interactions with tubulin [17][18][19]. The chain length may be important for a,b-unsaturated carbonyl compounds to penetrate the interior of tubulin.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to A-ring derivatives, these have minimal estrogen receptor binding affinity [21,22]. Various types of d-ring-modified estrone analogs have been synthetized and tested for possible inhibitory effects on cell proliferation [23][24][25], but these modifications were restricted to substitution with different functional groups at position 17 and dehydration at positions 14, 15 and 16. Until recently, no experimental data had been published in connection with the effect of d-ring expansion and substitution on the antiproliferative activity of the estrone derivatives, although they might be expected not to exhibit appreciable estrogen receptor binding affinity and therefore no estrogenic activity in vivo. Wölfling et al [26] reported the synthesis of normal and 13-epid-homoestrone and their 3-methyl ethers, and results on their estrogen and progesterone receptor binding abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Taking 2-methoxyestrodiol as an example, this compound inhibits tubulin polymerization with IC 50 of 5.3 μM in cell-free systems. Meanwhile, it is about 6 fold more potent than MT7 against tumor cell proliferation in vitro [56]. Proportionally, the concentration of MT7 should be more than 30 μM for 50% inhibition of tubulin polymerization.…”
Section: Discussionmentioning
confidence: 99%